Epidemiology of Sepsis-like Illness in Young Infants: Major Role of Enterovirus and Human Parechovirus. Issue 2 (February 2018) - de Jong, Eveline P.; van den Beuken, Monique G. A.; van Elzakker, Erika P. M.; Wolthers, Katja C.; Sprij, Arwen J.; Lopriore, Enrico; Walther, Frans J.; Brus, Frank
Abstract : Background: Sepsis-like illness is a main cause for hospital admission in young infants. Our aim was to investigate incidence, epidemiology and clinical characteristics of enterovirus (EV) and human parechovirus (HPeV) infections in young infants with sepsis-like illness. Methods: This is a prospective observational cohort study in which infants younger than 90 days of age, presenting with sepsis-like symptoms in a secondary care children's hospital, underwent a full sepsis work-up. Clinical signs and infectious indices were recorded. EV or HPeV RNA was detected by polymerase chain reaction in plasma and/or cerebrospinal fluid (CSF). Results: Infants were diagnosed with EV, HPeV, fever of unknown origin or severe infection. EV and HPeV were detected in 132 of 353 (37%) and 52 of 353 (15%) of cases, respectively. EV and HPeV have distinct seasonability. Some differences in clinical signs and symptoms occurred between children with EV and HPeV infection but were of limited clinical value. CSF pleocytosis occurred in 44% of EV positive infants, and only in 13% of those with HPeV infection. Conclusions: EV and HPeV infections are major causes of sepsis-like illness in infants < 90 days of age. Neither clinical characteristics nor laboratory indices were predictive for EV/HPeV infection. CSF pleocytosis occurs, but not in all patients. Testing for EV and HPeV in all young infants with sepsis-like illness is strongly advised. Abstract : Supplemental Digital Content is available in the text.